A SOLUBILITY ENHANCEMENT OF ACECLOFENAC BY NEW CRYSTALLIZATION TECHNIQUE - DN, CHETHAN PATEL; A, SHRENATH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present work aim was “A solubility enhancement of aceclofenac by new crystallization technique.” Aceclofenac is non-steroidal anti-inflammatory drug comes under bio-pharmaceutics classification system Class II with low solubility and high permeability. The aim of the study was to study the solubility and dissolution rate of the pure drug and prepared crystals at different temperature. Methods: Crystal of aceclofenac was prepared by antisolvent sonocrystallization technique. Results: A different crystal was prepared by Antisolvent sonocrystallization technique. The effect of solvents, temperature, and sonication was investigated. All the formulation was studied the dissolution behavior, MDT, %DE, and solid state characterization such as differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Conclusion: The solubility and dissolution rate of the prepared crystals were significantly higher than pure drug. The prepared crystals in ethanol at temperature 60°C±1°C showed the highest of the solubility of drug at 60 min. Among the prepared aceclofenac, crystals at 60 were showed better results with respect to MDT and %DE when compared to preparation of crystals at 10°±1°C and 25±1°C. DSC studies showed that there was no appreciable change in the melting endotherm of prepared crystals compared to that of pure drug. Powder XRD of prepared crystals at different temperature shows increases intensity of peaks compared to pure drug. SEM studies indicated that prepared crystals at different temperature using sonication shows are sharp needle in shape with crystalline surface compared to pure drug. The results indicate that antisolvent sonocrystallization serves as a successful strategy for enhancing poorly water soluble drug.